Assessment of the efficacy of α-lipoic acid in treatment of diabetes mellitus patients with erectile dysfunction: A protocol for systematic review and meta-analysis. Issue 36 (4th September 2020) - Cai, Jiawei; Chen, Junmin; Zeng, Qianqian; Liu, Jie; Zhang, Yanli; Cheng, Haiping; Yao, Shasha; Chen, Qiu
Abstract: Background: Diabetes mellitus with erectile dysfunction (DMED) is one of the most common causes of disability in diabetic population, and its pathogenesis is related to a variety of factors. Because its pathogenesis is complex and the existing treatment methods have limitations, DMED is difficult to treat in clinical. Recently, some studies have shown that α-lipoic acid (ALA) is associated with DMED, but there is no systematic review and meta-analysis on the relationship between ALA and DMED. Methods: We will search each database from the built-in until July 2020. The English literature mainly searches Cochrane Library, PubMed, EMBASE, and Web of Science, while the Chinese literature comes from CNKI, CBM, VIP, and Wangfang database. Simultaneously we will retrieve clinical registration tests and grey literatures. This study only screen the clinical randomized controlled trials (RCTs) about ALA for DMED to assess its efficacy. The 2 researchers worked independently on literature selection, data extraction, and quality assessment. The dichotomous data is represented by relative risk (RR), and the continuous is expressed by mean difference (MD) or standard mean difference (SMD), eventually the data is synthesized using a fixed effect model (FEM) or a random effect model (REM) depending on whether or not heterogeneity exists. Erectile dysfunction (ED) will be diagnosed by the International Index of Erectile Function 5 (IIEF-5) score. Finally, meta-analysis was conducted by RevMan software version 5.3. Results: This study will synthesize and provide high quality to evaluate the effectiveness of ALA supplementation for the treatment of DMED. Conclusion: This systematic review aims to provide new options for ALA supplementation treatment of DMED in terms of its efficacy and safety. PROSPERO registration number: INPLASY202070130.